Is the revolving door of Washington a back door to excess corporate returns? - Mehmet I. Canayaz; Jose Vicente Martinez; Han N. Ozsoylev (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
In this paper, we look into the so-called "revolving door of Washington", which is the movement of individuals between federal government positions and jobs in the private sector, and examine its link to long-run stock returns. We find that firms where current public officials become future employees outperform other firms by a statistically significant 7.43% per year in terms of four-factor alpha. This result is robust to different weighting methodologies and risk adjustments, and to plausible reverse causality arguments. We also show that firms receive more valuable government contracts from a government agency when a future firm employee is holding a post at that agency. Such financial gains are significantly reduced during periods in which presidential executive orders restrict revolving door movements. Our results are consistent with the notion that some public officials could be favoring certain companies while in office with a view to gaining future corporate employment.
Keywords: D73; G12; G18; L51; 330; corporate political connections; government contracts; regulatory capture; revolving door